Enhancing Spelling Performance in Students with Learning Disabilities - Nies, Keith A.; Belfiore, Phillip J. (Journal of behavioral education, 2006)
The present study, using a single subject adapted alternating treatments design, compared the effects of two spelling strategies (cover, copy, compare, and copy-only) used to enhance spelling performance in 2, third-grade students with learning disabilities. The cover, copy compare (CCC) method required the students to say the word, point to the word, repeat the word, cover the word, print the word, compare the word to the correct model, and correct errors if necessary. The copy-only method required the students to say the word, point to the word, repeat the word, and print the word. Overall, the CCC strategy was more effective in words learned and words retained. Results are discussed in light of CCC requiring a self-evaluation/self-correction component not required in the more traditional method of instruction. By incorporating a simple, self-management component to spelling instruction, teachers may improve spelling performance in the classroom.